The Impact of Labor Law Reform on Indonesian Workers: A Comparative Study After the Job Creation Law - Arinto Nugroho; Irfa Ronaboyd; Emmilia Rusdiana; Dicky Eko Prasetio; Sonny Zulhuda (Universitas Negeri Semarang, 2024)
This study is expected to have significant implications for policymakers and stakeholders in Indonesia and other developing countries seeking to reform their labor laws. The study can validate the development of new policies and programs to protect the rights of the workers, promote decent work, and provide greater access to social protection. The discussion on comparing labor regulations before and after implementing the Job Creation Law (The Law Number 6 Year 2023) in Indonesia covers several key aspects, including wage arrangements, outsourcing, social protection, and fixed-term employment agreements (PKWT). The Job Creation Law reflects the trend to provide more flexibility to employers, allowing them to customize working conditions according to business needs. While a push exists to improve the investment climate and create jobs, these changes raise serious questions about workers’ rights and welfare, particularly concerning about social protection and job security. This comparison indicates significant changes in Indonesia’s labor regulations, providing a clearer picture of workers’ challenges and opportunities. Labor law reform in Indonesia has impacted workers’ perception and responses. While some perceive it as a positive step that strengthens legal protection against unfair termination of employment, many workers still experience inequalities in access to health insurance, pensions, and workplace accident insurance. The government and stakeholders should work to improve workers’ access to social security and strengthen law enforcement and oversight to minimize potential implementation failures that could harm the rights of the workers.